ISMUBA-BTQ Learning Strategies for Improving Juz 30 Memorization among Elementary School Students - Bella Soni Ariani; Abdul Kholik (ITScience (Information Technology and Science), 2026)
This study aims to describe and analyze ISMUBA-BTQ learning strategies in improving students’ memorization of Juz 30 at SD Muhammadiyah 1 Margahayu and SD Al-Munawwaroh Ciparay, Bandung Regency. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving school principals, ISMUBA-BTQ teachers, students, and supporting informants. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing or verification. The trustworthiness of the data was ensured through credibility, transferability, dependability, and confirmability, supported by triangulation and member checking. The findings show that ISMUBA-BTQ learning strategies were implemented through systematic planning, structured implementation, formative evaluation, and continuous follow-up. The main strategies included talaqqi, muraja’ah, tasmi’, repetition, memorization deposits, reading correction, peer learning, and daily religious habituation. Supporting factors included teacher commitment, religious school culture, structured curriculum support, student motivation, parental involvement, and documentation of memorization progress. Meanwhile, inhibiting factors included limited instructional time, varied Qur’anic reading abilities, unstable motivation, lack of home muraja’ah, large student groups, and external distractions such as gadget use. This study concludes that effective ISMUBA-BTQ learning strategies require a balance between structured program management and adaptive guidance based on students’ learning readiness. Therefore, ISMUBA-BTQ learning should be strengthened as a comprehensive pedagogical system for developing Qur’anic literacy, religious discipline, and Islamic character among elementary school students.